Three‐dimensional coherent diffractive imaging on non‐periodic specimens at the ESRF beamline ID10. (17th March 2014) - Chushkin, Y.; Zontone, F.; Lima, E.; De Caro, L.; Guardia, P.; Manna, L.; Giannini, C.
<x xml:space="preserve">Abstract</x> The progress of tomographic coherent diffractive imaging with hard X‐rays at the ID10 beamline of the European Synchrotron Radiation Facility is presented. The performance of the instrument is demonstrated by imaging a cluster of Fe2P magnetic nanorods at 59 nm 3D resolution by phasing a diffraction volume measured at 8 keV photon energy. The result obtained shows progress in three‐dimensional imaging of non‐crystalline samples in air with hard X‐rays.